Hansel and Gretel = Hänsel und Gretel - Fisher, Burton D. (Opera Journeys mini guide series., 2000)
A comprehensive guide to Humperdinck's HANSEL AND GRETEL, featuring Principal Characters in the opera, Brief Story Synopsis, Story Narrative with Music Highlight Examples, and an insightful and in depth Commentary and Analysis by Burton D. Fisher, noted opera author and lecturer.